Immune responses during gestational malaria: a review of the current knowledge and future trend of research - Maestre, Amanda; Carmona-Fonseca, Jaime (The Journal of Infection in Developing Countries, 2014)
Women pregnant with their first child are susceptible to severe P. falciparum disease from placental malaria because they lack immunity to placenta-specific cytoadherence proteins. In subsequent pregnancies, as immunity against placental parasites is acquired, there is a reduced risk of adverse effects of malaria on the mother and fetus and asymptomatic parasitaemia is common. In the case of vivax malaria, with increasing reports of severe cases in Asia and South America, the effects of infection by this species during pregnancy remain to be elucidated. This review summarized the main aspects involved in the acquisition of specific antimalarial immune responses during pregnancy with emphasis in research carried out in America and Asia, in order to offer a framework of interpretation for studies on pregnant women with malaria which are recently being produced in these regions. The authors conclude that (1) Effective humoral responses during gestational malaria are mainly directed against variant surface antigens codified by genes of the var2Csa family of P. falciparum; (2) Acquisition of immunity against these variant antigens depends on the degree and intensity of transmission, and the chance increases with age and successive pregnancies; (3) Antibody development is guided by specific cellular immune responses in cases of placental and maternal infection, and (4) The study of the significance of acquisition of specific immunity against both P. falciparum and P. vivax in America, should be performed.